Gepants as a New Therapeutic Option for Migraine - Maziarczyk, Alicja; Lambach, Jakub; Kutnik, Kacper; Miazga, Dominika; Dąbrowska, Julia; Białogłowski, Michał; Mazurek, Katarzyna; Gęborys, Anna; Wojcieszak, Maja; Matuszewska, Julia (Quality in Sport, 2026)
Background. Migraine is a common neurological disorder characterized by recurrent, often unilateral, throbbing headaches accompanied by other symptoms. It arises from sensory processing disorders involving activation of the trigeminal-vascular system and release of pro-inflammatory neuropeptides such as calcitonin gene-related peptide (CGRP), which is a key therapeutic target. Gepants are small-molecule CGRP receptor antagonists that block CGRP-induced pain amplification in trigeminal pathways and other related structures. Their efficacy in migraine treatment has been the focus of many recent clinical studies. Aim. The aim of this study was to review the latest data on the therapeutic potential of gepants in acute and preventive migraine treatment, assess their safety profile, and compare their clinical utility with established therapies such as triptans and monoclonal antibodies targeting CGRP. Material and methods. We conducted a review of the literature from 2017-2025 available in the PubMed database, using the keywords “migraine,” “CGRP,” and “gepants.” Results. Clinical trials have shown that ubrogepant, rimegepant, and atogepant are effective in aborting acute migraine attacks, while rimegepant and zavegepant are effective in preventing migraines. Compared to currently available targeted therapies, they are less effective than triptans and comparably effective to monoclonal antibodies targeting CGRP. Conclusions. Gepants are a safe class of medications that can be used both for prevention and for aborting migraine attacks. Although less effective than triptans, they can be used in patients who cannot be treated with them. They also have a more convenient oral form of administration compared to monoclonal antibodies, with comparable efficacy. Further research is still needed to more accurately assess the efficacy of gepants, compare them to currently approved therapies, and evaluate their potential for application in clinical practice.